2005
DOI: 10.1172/jci24562
|View full text |Cite
|
Sign up to set email alerts
|

Fertility in luteinizing hormone receptor-knockout mice after wild-type ovary transplantation demonstrates redundancy of extragonadal luteinizing hormone action

Abstract: The luteinizing hormone receptor (LHR), mainly expressed in gonads, is essential for normal reproduction. However, numerous recent studies have also demonstrated LHR expression in multiple extragonadal reproductive and nonreproductive tissues. Although some effects of luteinizing hormone (LH) or its agonist, human chorionic gonadotropin, have been shown in extragonadal sites, their physiological significance remains open. In the present study, we have addressed the function of the extragonadal LHR using LHR-KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…A more recent study however, showed that LuRKO mice recovered most of their fertility potential and achieved pregnancy after orthotopic ovarian tissue transplantation using wild type ovaries [40]. Our patient had a successful pregnancy after using donor eggs supporting the findings reported by Pakarainen et al [40] that functional extragonadal LHCGR may not be indispensable for pregnancy. Whether the murine model is different from the human model and whether progesterone replacement in humans can compensate for the defective uterine LHCGR is unknown.…”
Section: P I F F C H L S C L Q S T S Y H S N Q Lsupporting
confidence: 89%
See 1 more Smart Citation
“…A more recent study however, showed that LuRKO mice recovered most of their fertility potential and achieved pregnancy after orthotopic ovarian tissue transplantation using wild type ovaries [40]. Our patient had a successful pregnancy after using donor eggs supporting the findings reported by Pakarainen et al [40] that functional extragonadal LHCGR may not be indispensable for pregnancy. Whether the murine model is different from the human model and whether progesterone replacement in humans can compensate for the defective uterine LHCGR is unknown.…”
Section: P I F F C H L S C L Q S T S Y H S N Q Lsupporting
confidence: 89%
“…Pregnancy was impaired in null mice following donor embryo transfer, even after estrogen and progesterone hormonal pretreatment and priming [39]. A more recent study however, showed that LuRKO mice recovered most of their fertility potential and achieved pregnancy after orthotopic ovarian tissue transplantation using wild type ovaries [40]. Our patient had a successful pregnancy after using donor eggs supporting the findings reported by Pakarainen et al [40] that functional extragonadal LHCGR may not be indispensable for pregnancy.…”
Section: P I F F C H L S C L Q S T S Y H S N Q Lsupporting
confidence: 87%
“…In conclusion, poorly developed secondary sex characteristics and infertility are observed in both sexes. Further detail about the phenotype of this model are in our previous reports (Zhang et al, 2001a;Zhang et al, 2003;Zhang et al, 2004;Pakarainen et al, 2005c;Pakarainen et al, 2005b;Pakarainen et al, 2005a).…”
Section: Lh/hcg-r Knockout (Lurko) Micementioning
confidence: 99%
“…Due to the difficulties in discriminating between direct and indirect actions of LH/hCG and to clarify the real functional significance of the extragonadal LH/hCG-R in vivo, we carried out orthotopic ovarian transplantations in LuRKO mice (Pakarainen et al, 2005a). We replaced bilaterally the ovaries of LuRKO mice with pieces of WT ovaries by a method described previously (Lavebratt et al, 1998) .…”
Section: Orthotopic Ovarian Transplantation In Lurko Micementioning
confidence: 99%
“…Although controversy exists on functional relevance of uterine LHCGRs with the existing Lhcgr mutant mouse models [30,31], the present results by Mitri et al establish that uterine LHCGRs are not indispensible for implantation and pregnancy maintenance in a single patient.…”
Section: Final Remarks and Future Directionsmentioning
confidence: 49%